2010
DOI: 10.24095/hpcdp.30.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Gender, social relationships and depressive disorders in adults aged 65 and over in Quebec

Abstract: The objective of this study was to examine if social relationships have a differential association with the presence of depression in men and women aged 65 and over. Data came from a survey of a representative sample of 2670 community-dwelling older adults in Quebec. Depressive disorders were measured using DSM-IV criteria. The prevalence of depression was 17.8% for women and 7.6% for men. Men reported a greater diversity of ties but less support than women. Having a confidant and/or being engaged in a good ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Our findings regarding the characteristics of older adults suffering from depressive symptoms reinforce those of other studies regarding the risk factors of being female, being older, and living alone [13][14][15][16][17][18][19][20][21][22]. We showed that depressive symptoms are associated with an increased disability burden in older adults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings regarding the characteristics of older adults suffering from depressive symptoms reinforce those of other studies regarding the risk factors of being female, being older, and living alone [13][14][15][16][17][18][19][20][21][22]. We showed that depressive symptoms are associated with an increased disability burden in older adults.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have also identified risk factors for symptoms of late-life depression that include demographic characteristics, such as female gender and higher age [13,[15][16][17][18][19], chronic medical illnesses [20], physical impairment, frailty, poor self-rated health [21,22], and distressing family and life events [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Severity of depression (major or minor) was estimated using the ESA Diagnostic Questionnaire (ESA-Q), a computer questionnaire developed by the research team (Préville, et al, 2008) �sing DSM-IV criteria (American Psychiatric Association, 1994). Description of this s�rvey an� severity of the �epression is availa�le in previo�s p��lications (Préville, et al, 2008;Mechakra-Tahiri, et al, 2009;Mechakra-Tahiri, Zunzunegui, Préville, & Dubé, 2010). A 12-month recall perio� �as �se�.…”
Section: Methodsmentioning
confidence: 99%